Development of copper-doped TiO2 photocatalyst for hydrogen production under visible light - Leong, Siew Yoong (Elsevier, 2009)
The advantage of copper doping onto TiO2 semiconductor photocatalyst for enhanced hydrogen generation under irradiation at the visible range of the electromagnetic spectrum has been investigated. Two methods of preparation for the copper-doped catalyst were selected – complex precipitation and wet impregnation methods – using copper nitrate trihydrate as the starting material. The dopant loading varied from 2 to 15%. Characterization of the photocatalysts was done by thermogravimetric analysis (TGA), temperature programmed reduction (TPR), diffuse reflectance UV-Vis (DR-UV-Vis), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Photocatalytic activity towards hydrogen generation from water was investigated using a multiport photocatalytic reactor under visible light illumination with methanol added as a hole scavenger. Three calcination temperatures were selected – 300, 400 and 500 C. It was found that 10 wt.% Cu/TiO2 calcined at 300 C for 30 min yielded the maximum quantity of hydrogen. The reduction of band gap as a result of doping was estimated and the influence of the process parameters on catalytic activity is explained.